HUBUNGAN KELENGKAPAN PENGISIAN RESUME MEDIS RAWAT INAP DENGAN PERSETUJUAN KLAIM BPJS DI RUMAH SAKIT SUMBER WARAS CIREBON - Asih Kundari (Sekolah Tinggi Ilmu Kesehatan Mitra Husada Karanganyar, 2025)
Hospitals are health service agencies that are abliged to provide comprehensive health services, to support this hospitals need to have medical records as administrative data. The medical records needs to have complete and accurate data to support the service process and the smoth process of caliming BPJS. This study aims to analyze the completeness of the BPJS inpatient medical resume at the Siloam Hospital, Jakarta.The research method used is quantitative method with descriptive statistics. The data collection method used is by observation, document and interviewa which hava a close relevance to the subject matter. From the research conducted, there are several problems including : incomplete writing of medical resumes illegibility of writing medical diagnoses incomplete writing of clear names and signatures of doctors and nurses who treat patients. The suggestions given to overcome the existing problems are : there is coordination between medical recors units and PPA(Professional Care Providers) socialization about the importance of completing medical record forms forming a medical records review team.